Binding selectivity and separation of p-functionalized toluenes with a metallo-cavitand in water. Issue 51 (21st May 2020) - Rahman, Faiz-Ur; Yang, Ji-Min; Wan, Yun-Hui; Zhang, Hui-Bin; Petsalakis, Ioannis D.; Theodorakopoulos, Giannoula; Rebek, Julius; Yu, Yang
Abstract : A metallo-cavitand is investigated for selective p -functionalized toluene isomer separation from its mixture with o - and/or m -isomers. Abstract : A metallo-cavitand (1-2Pd ) showed unprecedented binding selectivity and sequestration of p -functionalized toluene isomers in water. The host–guest complexation was studied using 1 H and COSY NMR methods and xylene-isomer complexes were examined by using DFT calculations. A liquid–liquid extraction scheme was developed for the separation of p -functionalized toluenes.